Presepsı Guru Dan Sıswa Terhadap Penerapan Pembelajaran Berdıferensıası Berbasıs Project Mata Pelajaran Senı Budaya Merdeka Belajar - vera angelina pasik pesik; Andi Imrah Dewi; Arif Firmansyah; Kadek Hariana (Jurnal Elementaria Edukasia, 2024)
This research aims to determine the Teachers' and students' perceptions of the implementation of project-based differentiated learning in arts and culture subjects, the concept of independent learning in class IV at SDN 15 Palu. This research uses qualitative research with descriptive methods. Data collection techniques use observation, interviews, questionnaire distribution and documentation. Based on the research results, the researchers obtained findings including that the perceptions of teachers and students regarding the implementation of project-based differentiated learning in class IV at SDN 15 Palu were very good. Although project-based differentiated learning has not been implemented well and according to the actual concept. However, the homeroom teacher for class IV was very satisfied with the results of implementing this learning, because it was able to create an active and enjoyable class atmosphere. So that existing learning objectives can be achieved well. Meanwhile, students' perceptions or responses to the application of differentiated learning are also very good, seen from the responses given by students during the learning process and based on the results of the questionnaire which shows that; Of the 28 students, 96.43% of students felt happy, interested and understood the learning that had taken place. only 5 people felt bored during the learning process, and as many as 24 people or 85.71% of students wanted this kind of learning to always be applied in their class. So it can be concluded that the response of teachers and students to the application of differentiated learning is very good, in fact it has a very big impact on the learning process in the classroom.